Business innovation in Asia : - McNamara, Dennis L. (Routledge, 2009)
The central concept of this volume, "knowledge networks," refers to interactive linkages around nodes of tacit and codified knowledge embedded in Global Value Chains. Such networks can be distinguished by the process or format of information exchange, the organization of the networks within firms, and by target market or product.